The effect of garlic and stevia extract with aerobic exercise on hypothalamic leptin and ghrelin receptor mRNA expression and insulin resistance in obese rats - Zohre Amirkhani; Armin Morteza Gholi; Sara Asghari; Danial Hakak; Mahdi Pouryousef; Behrooz Yahyaei; Sayyed-Javad Ziaolhagh (BMC Complementary Medicine and Therapies)
Abstract Background Obesity has recently become the most prevalent diet-related disease worldwide. This study aimed to investigate the effects of aerobic exercise, stevia, and garlic extract on leptin and ghrelin receptor mRNA, as well as the interactions between insulin and glucose in relation to these genes. Methods A total of 50 male Wistar rats were split into two groups: one group was fed regular rodent food, while the other was fed a high-fat diet for 12 weeks to induce obesity. The obese rats were then divided into six groups of five (N = 5) based on Lee’s index: an obese control group (OC), obese treated with garlic, stevia (OGS), obese aerobic exercise (OE), obese garlic and aerobic exercise (OGE), Obese stevia and aerobic exercise (OSE), and a Normal weight group (NC). The exercise groups participated in a gradually increasing aerobic walking program, whereas the stevia and garlic groups received daily oral doses of their respective extracts. The expression of leptin and ghrelin receptor genes in the hypothalamus was measured using real-time PCR, and insulin resistance was calculated using the HOMA/IR formula. Statistical analysis was conducted using ANOVA, with a significance level set at P < 0.05. Results The obese (O) rats experienced a significant increase in body weight compared with the control (C) rats (p = 0.013), whereas the treated rats showed no significant changes in weight. Leptin receptor mRNA levels were significantly lower in O rats than in C rats (p = 0.00), but increased significantly in the OS (p = 0.000) and OSE (p = 0.034) groups compared with obese rats. Ghrelin receptor mRNA levels were significantly higher in the O group than in the C group (p = 0.035), but decreased in all treatment groups, with the OE (p = 0.001), OGE (p = 0.001), and OSE (p = 0.004) groups showing the greatest reductions. Insulin resistance increased slightly in the O group compared with the C group (p = 0.112), but was lowest in the OS group among all groups (p = 0.018). Conclusions Stevia significantly improved leptin and ghrelin receptor mRNA expression, glucose levels, and insulin resistance in obese rats, showing its potential as an effective dietary intervention for managing obesity.